2016
DOI: 10.1016/j.ijhydene.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Water management in novel direct membrane deposition fuel cells under low humidification

Abstract: Direct membrane depositionNeutron radiography Water management Back diffusion a b s t r a c t Polymer electrolyte membrane fuel cells (PEMFCs) fabricated by direct membrane deposition (DMD) were shown to work even at dry conditions without significant deterioration of the membrane resistance. Here, in situ neutron radiography is used to investigate the water management in those fuel cells to uncover the phenomena that lead to the robust operation under low humidification. A constant level of humidification wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 24 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…52 HFR is an index for the level of water uptake by a membrane and its associated conductivity. 49 The HFR initially decreases from ∼270 Ω cm 2 at 0.85 V to ∼150 Ω cm 2 at 0.55 V due to an increase in the hydration with increasing current. Later, HFR increases from ∼150 Ω cm 2 at 0.55 V to ∼175 Ω cm 2 at 0.3 V as a result of membrane dehydration due to increased temperatures at higher currents, which is a known trend from our previous work.…”
Section: Resultsmentioning
confidence: 95%
“…52 HFR is an index for the level of water uptake by a membrane and its associated conductivity. 49 The HFR initially decreases from ∼270 Ω cm 2 at 0.85 V to ∼150 Ω cm 2 at 0.55 V due to an increase in the hydration with increasing current. Later, HFR increases from ∼150 Ω cm 2 at 0.55 V to ∼175 Ω cm 2 at 0.3 V as a result of membrane dehydration due to increased temperatures at higher currents, which is a known trend from our previous work.…”
Section: Resultsmentioning
confidence: 95%
“…For example, Kong et al [65,66] enhanced the self-humidification by adopting double gas diffusion backing layers. Recently, Breitwieser et al [67] fabricated a PEMFC with direct membrane deposition [68] which facilitates the back diffusion from the cathode to the anode. The neutron radiography test was carried out and it is shown that the humidification level of the MEA stay constant even with dry anode and low cathode RH (15%).…”
Section: Other Methodsmentioning
confidence: 99%
“…This is also in agreement with previous work, where significantly reduced values of R LF-HF were found for DMD fuel cells with a pure Nafion membrane, [31,44] in particular at high current densities. [33,46] Comparable improvements were reported for patterned membranes enhancing the catalyst layer/PEM interaction. [33,46] Comparable improvements were reported for patterned membranes enhancing the catalyst layer/PEM interaction.…”
Section: Beginning Of Test/ End Of Test -Analysismentioning
confidence: 99%